Heuristics in energy judgement tasks - Van den Broek, Karlijn; Walker, Ian (Journal of environmental psychology, 2019)
To save energy effectively, householders need to be aware of the energy consumption in their homes, in particular the energy use of their household appliances. People's perception of the energy use of their appliances has been found to be influenced by the use of heuristics (simple rules for making quick decisions), yet these heuristics have received little research attention. Three studies investigated the use of these energy judgement heuristics using mixed methods. Findings show that 1) participants used as many as twenty-four different heuristics in an energy judgement task - an order of magnitude more than identified in existing literature; 2) participants are aware they use the heuristics, but awareness varies per heuristic; 3) the use of these heuristics can be changed and this in turn can improve energy literacy. These studies demonstrate for the first time that the energy judgement process is much more complex than previously thought and provides a promising starting point for future research to uncover opportunities to improve energy literacy.
Gesehen am 10.05.2019